Validity of the family Anacardiaceae encyclopedia book: A development research - Fatimatul Zahro; Muhammad Zaini; Riya Irianti (Practice of The Science of Teaching Journal: Jurnal Praktisi Pendidikan, 2024)
Learning using encyclopedia books based on the potential of an area is one solution used to overcome problems that often arise in biology learning, one of which is students' low critical thinking ability. Developing an encyclopedia book in the Coastal Forest Area of ​​Tabanio Village is an example of how 21st-century learning emphasizes the importance of an environmental perspective in learning. This strategy combines the idea of ​​working locally while thinking globally. An encyclopedia is an educational resource that uses text and images to explain a subject. This research aims to verify the encyclopedia of the Anacardiaceae family, which may be found in the Coastal Forest of Tabanio Village. This research uses the Tessmer formative assessment design combined with Educational Design Research (EDR). Some validated components are coherence, readability, redundant vocabulary, active and passive sentences, value protection, applicability, and device implications. Encyclopedia experts researched three experts from the Biology Education study program at Lambung Mangkurat University. This research focuses on the Anacardiaceae family encyclopedia. The findings of this research demonstrate the validity (feasibility) of the encyclopedia of the Anacardiaceae family in the Coastal Forest of Tabanio Village. Therefore, this encyclopedia book can be used as an alternative learning resource and can be used to help improve students' critical thinking. Abstrak. Pembelajaran dengan menggunakan buku ensiklopedia berdasarkan potensi yang dimiliki sebuah daerah merupakan salah satu solusi yang digunakan untuk mengatasi permasalahan-permasalahan yang sering muncul pada pembelajaran biologi salah satunya rendahnya kemampuan berpikir kritis mahasiswa. Pengembangan buku ensiklopedia di Kawasan Hutan Pesisir Desa Tabanio merupakan contoh bagaimana pembelajaran abad 21 menekankan pentingnya perspektif lingkungan dalam pembelajaran. Strategi ini menggabungkan gagasan bekerja secara lokal sambil berpikir secara global. Ensiklopedia adalah sejenis sumber pendidikan yang menggunakan teks dan gambar untuk menjelaskan suatu subjek. Penelitian ini bertujuan untuk memverifikasi ensiklopedia famili Anacardiaceae yang mungkin ditemukan di Hutan Pesisir Desa Tabanio. Penelitian ini menggunakan desain penilaian formatif Tessmer yang dipadukan dengan Educational Design Research (EDR). Koherensi, keterbacaan, kosakata yang berlebihan, kalimat aktif dan pasif, perlindungan nilai, penerapan, dan implikasi perangkat merupakan beberapa komponen yang divalidasi. Pakar ensiklopedia meneliti tiga orang ahli program studi Pendidikan Biologi Universitas Lambung Mangkurat. Penelitian ini fokus pada ensiklopedia famili Anacardiaceae. Temuan penelitian ini menunjukkan validitas (kelayakan) ensiklopedia famili Anacardiaceae di Hutan Pantai Desa Tabanio. Oleh karena itu, buku ensiklopedia ini dapat dijadikan salah satu alternatif sumber belajar dan dapat dimanfaatkan untuk membantu meningkatkan mahasiswa dalam berpikir kritis.